PENGARUH PENGANGGARAN PARTISIPATIF, KEJELASAN SASARAN ANGGARAN, DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA MANAJERIAL - Akhmad Saebani; Nugrahini Lastiningsih (Ekonomi dan Bisnis, 2015)
This study aims to test empirically the effect of participative budgeting, budget goal clarity, and organizational commitment on managerial performance. Research using primary data obtained through a questionnaire. The population in this study is a course of study at a private university in the region Kopertis III by sampling using simple random sampling. Samples that returned 57 of the 87 sent (response rate 66%). Data were analyzed using multiple linear regression were processed using SPSS. Results of this study indicate that; 1) participative budgeting significant positive effect on managerial performance; 2) budget goal clarity significant positive effect on managerial performance; and 3) organizational commitment is not significant positive effect on managerial performance.